Implementation of Funding Risk Management in Sharia Banking - Lutfiatul Ulfa Agnesa; Sri Wigati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Activities in the banking world are very susceptible to risk. Especially in fundraising activities because it is closely related to the bank's operations itself. To minimize risk, risk management is needed. This purpose of this paper to determine the implementation of funding risk management at BSI KCP Kediri Hayam Wuruk. The research method used is qualitative research using field observations to collect relevant data and analyze it comprehensively. Data collection was carried out through interviews with funding officer Bank BSI KCP Kediri Hayam Wuruk, and literature studies taken from literature sources relevant to the topic. The research results show that there are 3 funding risk management, namely liquidity risk, reputation risk and return risk. The ways to manage these risks are, 1. Liquidity risk by identifying funding and asset structures, 2. Reputation risk by improving service and managing customer complaints in a timely manner and complying with regulations according to sharia principles, 3. Return risk by managing customer expectations and improving the best service to customers.